Assessing reflective thinking skills in EFL/ESL instructors based on differences in graduation degree and nationality. Issue 6 (1st November 2016) - Marzban, Amin; Ashraafi, Neda
Abstract: The present study aimed to explore the differences among EFL/ESL (English as a Foreign Language/English as a Second Language) instructors while applying reflective thinking skills in terms of graduation degree and nationality. It employed a descriptive design through survey questionnaire. To this end, upon cluster sampling, 200 Iranian and American instructors first responded to Akbari, Behzadpoor, and Dadvand's inventory followed by an open-ended questionnaire (RTOQ) based on Dymoke and Harrisons' remarks. Results revealed a significant difference in applying reflective thinking skills concerning academic degree and nationality among participants and indicated a crucial role for nationality and culture in ELT (English Language Teaching) contexts. Graduation degree left a significant effect on instructors' competencies and attitudes while applying thinking skills. The study highlighted the importance of incorporating reflective skills as a core component of pedagogical systems. Furthermore, the results laid further proof to the role that integrating thinking skills into pedagogy would play in determining the learning direction.